INOVASI KREATIF BERBASIS DAUR ULANG: PENGABDIAN MASYARAKAT DI BRSBKL DINSOS MELALUI PEMBUATAN KALENDER ASA - Arum Isnatasari; Maula Nuriyatul Azizah; Auliya Hanifah (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2025)
Creativity has an important role in helping social rehabilitation for fostered community of the Bina Karya and Laras Social Rehabilitation Center (BRSBKL). The "Asa Calendar" program was implemented to improve participants' skills and self-confidence through creative activities that utilize recycled goods. This activity began with a field survey to find out what the participants needed, followed by training of calendar making, involving 29 participants, 3 assistants, and 3 trainers from UIN Sunan Kalijaga Yogyakarta students. Training included technical explanations, hands-on practice, and guidance during the manufacturing process. The materials used are discarded cardboard, recycled wire, styrofoam, white glue, double tape, and ice cream sticks. The tools used consist of scissors, black marker and cutting pliers. The results of this community service activity showed that participants are able to create useful calendars and help reduce waste. This program gave a positive impact in improving skills, building cooperation, and raising awareness of the importance of protecting the environment. It is hoped that this activity can become an example of effective and sustainable community empowerment, as well as inspire the use of creativity-based activities in various other social rehabilitation contexts.